2019
DOI: 10.1519/jsc.0000000000001884
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cold Water Immersion Performed on Successive Days on Physical Performance, Muscle Damage, and Inflammatory, Hormonal, and Oxidative Stress Markers in Volleyball Players

Abstract: The aim of this study was to investigate the effects of daily cold water immersion (CWI) on physical performance, muscle damage, and inflammatory, hormonal, and oxidative stress markers in volleyball. Six players were submitted to CWI and six players to a placebo, during 5 training days. Thigh circumference, squat jump, and agility were measured on the 1, 3 and 6 days. On the 1 and 6 days, blood and saliva were collected for analysis of oxidative stress, muscle damage, and inflammatory and hormonal levels. Mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 42 publications
5
42
2
Order By: Relevance
“…SJ and CMJ performances were undertaken to determine athletes’ explosive power ( de Freitas et al, 2017 ). Jumps were assessed using an infrared jump system (Optojump, Microgate ® , Bolzano, Italy) interfaced with a microcomputer.…”
Section: Methodsmentioning
confidence: 99%
“…SJ and CMJ performances were undertaken to determine athletes’ explosive power ( de Freitas et al, 2017 ). Jumps were assessed using an infrared jump system (Optojump, Microgate ® , Bolzano, Italy) interfaced with a microcomputer.…”
Section: Methodsmentioning
confidence: 99%
“…It is possible that the self-selected arm swings employed by the good and poor CFDR values were characterized by different ranges of motion and/or angular velocities, thereby influencing the comparison of relative muscle responses. In addition, despite similar height and mass characteristics in SCBV and HCIV athletes, it is possible that different body compositions further challenged the present assessment of relative muscle responses, as differences in fatigue, blood flow, and hydration status could dramatically influence EMG signals [18,19]. Even though these considerations should be addressed in subsequent evaluations, the current study indicates that relative muscle responses might not be a distinguishing feature of good in comparison with poor CMJ performance [7,8].…”
Section: Discussionmentioning
confidence: 76%
“…Other studies with healthy subjects to evaluate the force, muscle work, and exit power during the vertical jump demonstrated that the vastus medialis muscle exerted major force and work during the jump accompanied by the gluteus maximus, rectus femoris, and medial gastrocnemius muscles [19,31]. The analysis also revealed that the single-joint muscle groups contributed considerably more during the jump when compared with bi-articulated muscles, and that the adductors, abductors, and external rotators were always activated, although their mechanical response during the jump work was minor [9,31].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations